Cobalt and magnesium ferrite nanoparticles: preparation using liquid foams as templates and their magnetic characteristics - Bala, Tanushree; Sankar, C. R.; Baidakova, Marina; Osipov, V.; Enoki, Toshiaki; Joy, Pattayil Alias; Bhagavatula L. V. Prasad; Sastry, M. (Langmuir, 2005)
An easy and convenient method for the synthesis of cobalt and magnesium ferrite nanoparticles is demonstrated using liquid foams as templates. The foam is formed from an aqueous mixture of an anionic surfactant and the desired metal ions, where the metal ions are electrostatically entrapped by the surfactant at the thin borders between the foam bubbles and their junctions. The hydrolysis is carried out using alkali resulting in the formation of desired nanoparticles, with the foam playing the role of a template. However, in the formation of ferrites with the formula MFe2O4, where the metal ion and iron possess oxidation states of +2 and +3, respectively, forming a foam from a 1:2 mixture of the desired ionic solutions would lead to a foam composition at variance with the original solution mixture because of greater electrostatic binding of ions possessing a greater charge with the surfactant. In our procedure, we circumvent this problem by preparing the foam from a 1:2 mixture of M2+ and Fe2+ ions and then utilizing the in situ conversion of Fe2+ to Fe3+ under basic conditions inside the foam matrix to get the desired composition of the metal ions with the required oxidation states. The fact that we could prepare both CoFe2O4 and MgFe2O4 particles shows the vast scope of this method for making even multicomponent oxides. The magnetic nanoparticles thus obtained exhibit a good crystalline nature and are characterized by superparamagnetic properties. The magnetic features observed for CoFe2O4 and MgFe2O4 nanoparticles are well in accordance with the expected behaviors, with CoFe2O4 particles showing higher blocking temperatures and larger coercivities. These features can easily be explained by the contribution of Co2+ sites to the magnetocrystalline anisotropy and the absence of the same from the Mg2+ ions.

Magnetic properties of the self-doped lanthanum manganites La1-xMnO3 - Sankar, C. R.; Joy, Pattayil Alias (Physical Review B, 2005)
The magnetic properties of different compositions in the self-doped lanthanum manganites, La1-xMnO3, have been studied by ac susceptibility and dc magnetization measurements in the temperature range 10-300 K. All compositions with x < 0.125 show an anomalous decrease in the ac susceptibility and zero field cooled (ZFC) dc magnetization at low temperatures, below the ferromagnetic ordering temperature. The temperature below which this anomalous behavior is observed, T-a, varies with the degree of La vacancy in the series where the Mn4+ concentration decreases with increasing x. Moreover, T-a varies with the Mn4+ content for a given composition. However, in both cases, this temperature levels off when the concentration of Mn4+ is above 23%. The magnetic-transition-like feature broadens and shifts to further lower temperatures with increasing magnetic fields and vanishes when measured above a certain field. A small but drastic increase in the coercivity is observed below T-a. There is a direct correlation between the shapes of the curves of the inverse of the coercivity as a function of temperature and ac susceptibility, indicating the influence of magnetic anisotropy on the characteristics of the ac susceptibility and zero field cooled magnetization curves of the self-doped compounds. The direct correlation between the changes in the coercivity and ac susceptibility as well as ZFC magnetization when measured at low magnetic fields give evidence to the role of domain wall pinning effects, which varies with the degree of self-doping or Mn4+ concentration.

Superspin glass behavior of a nonstoichiometric lanthanum manganite LaMnO3.13 - Sankar, C. R.; Joy, Pattayil Alias (Physical Review B, 2005)
Aging and memory effects are observed in an oxygen nonstoichiometric lanthanum manganite LaMnO3.13 from time-dependent dc magnetic measurements by employing various cooling protocols. The results can be best described by the superspin glass model of interacting magnetic nanoparticles system. The possible origin of such a behavior is the confinement of interacting small magnetic clusters formed as a result of the formation of manganese vacancies, along with the random distribution of tetravalent manganese ions in the lattice.